Analisis Gesture Siswa dalam Pemecahan Masalah Geometri secara Berkelompok Ditinjau dari Tahapan Berpikir Van Hiele - Mulbar, Usman; Rosidah; Sahid; Wazithah T., Mar Athul (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
This study addresses the problem of students’ low mathematical literacy, particularly in relation to problem-solving strategies and creativity in solving contextual mathematical tasks. The research aims to describe students’ problem-solving strategies and creativity based on their levels of mathematical ability in solving mathematical literacy problems. This study employed a descriptive qualitative approach involving six seventh-grade junior high school students selected through purposive sampling and categorized into high, intermediate, and low mathematical ability groups. Data were collected through mathematical literacy tests and semi-structured interviews, then analyzed using indicators of creativity (fluency, flexibility, and novelty) and problem-solving strategies. The findings reveal that high-ability students fulfilled all three creativity indicators by applying varied, appropriate, and original strategies. Intermediate-ability students generally achieved two indicators, mainly fluency and flexibility or fluency and novelty, but showed limitations in consistently demonstrating all aspects of creativity. In contrast, low-ability students struggled to understand contextual problems, selected inappropriate strategies, and did not meet any of the creativity indicators. The discussion highlights that mathematical ability strongly influences students’ strategic behavior and creative performance in solving literacy-based problems. In conclusion, students’ problem-solving strategies and creativity are proportional to their mathematical ability levels. Therefore, instructional practices that explicitly promote diverse strategies and creative thinking are essential to enhance students’ mathematical literacy skills.